Hacking in the cloud. Issue 1 (26th November 2018) - Gregorio, Nick; Mathanamohan, Janahan; Mahmoud, Qusay H.; AlTaei, May
Abstract : Cloud computing is a widely expanding and rapidly adopted field of technology. The ability to grant significantly more computational resources than a single machine allows, through use of virtual machines, is incredibly helpful to enterprises that need to meet the demands of hundreds of thousands of concurrent users. However, just as these resources can be used for meaningful purposes, they can also be used for malicious attacks. In this paper, we present the legal and ethical challenges of hacking in the cloud citing specific cyber laws from Canada and the United Arab Emirates, along with the terms of use of cloud service providers. We also present the results of a legal SYN (synchronization) flood attack experiment, utilizing packets with spoofed source internet protocol addresses to determine if this attack works on a cloud service provider. We offer recommendations based on whether or not the cloud platform provides sufficient utility to be used in aiding hackers with their tasks, or if the legal and ethical issues surrounding the implementations ruin any opportunities before development even begins.